The Role Of Religious Education In The Formation Of Children's Moral And Ethics Through Habituation At Mother's Prayer Kindergarten, Kepahiang Regency - Pratiwi, Lidia; Asnawati, Asnawati; Haryono, Mimpira (Early Childhood Research and Practice, 2025)
The purpose of this research is to analyze the role of religious education in the formation of moral and ethics through habituation at Doa Ibu Kindergarten in Kepahiang Regency. This study is qualitative research that aims to describe an ongoing research process. The main subjects of this research are the accompanying teachers, totaling 3 individuals. Data collection techniques employed include observation, interviews, and documentation. The data analysis technique used in this research involves data reduction and data display analysis techniques. The conclusion of this study indicates that the efforts made by teachers in assisting the formation of moral and ethics in the kindergarten have been implemented effectively.